The Repetition of a Singularity: Phenomenology of Déjà Vu (Phenomenology, Humanities and Sciences, 2024)
Phenomenology aims at analyzing the constitutive moments of the different experiences by doing justice to their specific ways of appearing. By doing so, it can make visible (and therefore correct) the problematic assumptions taken as valid from the outset. These assumptions coherently distort and manipulate the phenomena in such a way that the phenomena are transformed into something radically different. The phenomenon of déjà vu is very interesting in this regard for two different reasons. Déjà vu is transformed into a different phenomenon in the field of cognitive sciences: déjà-vu is commonly understood as a simple memory error. Secondly, déjà vu implies a repetition of a unique, contingent experience. This logic of repetition is not easily compatible with the logos of empirical sciences that focus on the identification of invariant relations between general terms through experimental research and therefore requires a different approach.
Keywords: Contemporany Philosophy; Phenomenology; Cognitivies Sciences; Déjà Vu; Repetition